Clinical Characteristics of Patients With Neuromyelitis Optica Spectrum Disorders With Early Onset. (August 2019) - Fragoso, Yara Dadalti; Sousa, Nise Alessandra C.; Saad, Tania; Alves-Leon, Soniza Vieira; Pimentel, Maria Lucia V.; Goncalves, Marcus Vinicius M.; Stella, Carla Vieira; Diniz, Denise Sisterolli; Santos, Gutemberg C.; Gomes, Sidney; Adoni, Tarso; Anacleto, Andrea; et al.
Neuromyelitis optica spectrum disorder is a severe and disabling disease that manifests with severe relapses of optic neuritis, longitudinally extensive myelitis, and/or brainstem syndromes. The disease is complex and, although onset typically occurs in middle age, children and adolescents may be affected. The present study adds to the literature through detailed clinical data from 36 Brazilian patients with neuromyelitis optica spectrum disorder starting before age 21. This was a retrospective assessment of medical records from 14 specialized units in Brazil. The results showed that the course of neuromyelitis optica spectrum disorder was worse in patients with disease onset before the age of 12 years. Gender and ethnic background did not influence disability accumulation. Over a median period of 8 years, 14% of the patients who presented the initial symptoms of neuromyelitis optica spectrum disorder before the age of 21 years died. In conclusion, the present study adds to the reports from other authors examining the severity of early-onset neuromyelitis optica spectrum disorder.